Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction - Lehmann, Tim; Büchel, Daniel; Mouton, Caroline; Gokeler, Alli; Seil, Romain; Baumeister, Jochen (Frontiers in Human Neuroscience, 2021)
Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction, little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients six weeks following anterior cruciate ligament reconstruction. A total of 12 patients after anterior cruciate ligament reconstruction (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 kg) and another 12 gender, age and activity matched healthy controls participated in this study. All subjects performed 10 x 30 sec. single leg stances on each leg, equipped with 64-channel mobile electroencephalography. Postural stability was quantified by area of sway and sway velocity. Estimations of the weighted phase lag index were conducted as a cortical measure of functional connectivity. The findings showed significant group × leg interactions for increased functional connectivity in the ACL injured leg, predominantly including fronto‐parietal (F(1, 22) = 8.41, p ≤ .008, η2 = .28), fronto‐occipital (F(1, 22) = 4.43, p ≤ .047, η2 = .17), parieto‐motor (F(1, 22) = 10.30, p ≤ .004, η2 = .32), occipito‐motor (F(1, 22) = 5.21, p ≤ .032, η2 = .19) and occipito‐parietal (F(1, 22) = 4.60, p ≤ .043, η2 = .17) intra‐hemispherical connections in the contralateral hemisphere and occipito‐motor (F(1, 22) = 7.33, p ≤ .013, η2 = .25) on the ipsilateral hemisphere to the injured leg. Higher functional connectivity in patients after anterior cruciate ligament reconstruction, attained by increased emphasis of functional connections incorporating the somatosensory and visual areas, may serve as a compensatory mechanism to control postural stability of the injured leg in the early phase of rehabilitation. These preliminary results may help to develop new neurophysiological assessments for detecting functional deficiencies after anterior cruciate ligament reconstruction in the future.